Influenza type A virus neuraminidase does not play a role in viral entry, replication, assembly, or budding. - Liu, C (1995)
We have used a neuraminidase-deficient influenza virus, NWS-Mvi, which was selected by supplying bacterial neuraminidase in the medium (C. Liu and G. M. Air, Virology 194:403-407, 1993), to define the role of neuraminidase in influenza virus replication. Electron microscopy showed that virions of the NWS-Mvi mutant assembled normally and formed large aggregates associated with cell surfaces. The NWS-Mvi virus grown in the absence of neuraminidase was able to carry out a second round of replication in MDCK cells without added neuraminidase, indicating that the virus particles contained in these aggregates were infectious. Aggregates of virus were also found in cytoplasmic vacuoles. When virus-infected cells were incubated in the presence of ferritin, such aggregates were found to be labeled with ferritin, indicating that they are derived from uptake at the cell surface. When the neuraminidase-deficient virus was administered intranasally to C57BL/6 mice, low titers of virus were recovered from the lungs and major histocompatibility complex class I-restricted cytotoxic T cells were generated: evidence that cells were infected in vivo. In C57BL/6 nu/nu mice, the low level of virus persisted for at least 28 days but never increased. These results suggest that neuraminidase is not required for influenza virus entry, replication, or assembly in cell culture or in mice.